APPLICATION OF THE PROJECT-BASED LEARNING MODEL TO IMPROVE STUDENT LEARNING OUTCOMES IN MIN 5 MEDAN - Muhammad Iqbal Nurfikri; Nashran Azizan; Hamidah . (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2022)
The learning process cannot be separated from assessment; if it is carried out well, it will get good grades. So that the learning process is carried out well, choose the suitable learning model in the 21st-century era. Because the learning model becomes a design pattern that aims to achieve learning objectives, student learning outcomes get excellent grades. The purpose of the study was to improve Pancasila and Civics education outcomes in aspects of spiritual attitudes, social attitudes, knowledge, and skills of students by applying PjBL learning models in material about obligations, rights, and responsibilities as citizens. The research subjects were class 6-A MIN 5 Medan students, 27 people. This research uses Kurt Lewin's classroom action research method. They collect data using tests, observations, and interviews. Data were analyzed descriptively with qualitative and quantitative approaches assisted by STATCAL software. The study's results proved that students experienced an increase in their learning outcomes with a value of 88.88% in cycle III through applying the PjBL learning model.Keywords: learning outcomes, learning model, 21st-century skills, PjBL, Pancasila and civic education.